Natural convection on heat transfer flow of non-newtonian second grade fluid over horizontal circular cylinder with thermal radiation - Prasad, V. Ramachandra; Bhuvanavijaya, R.; Bandaru, Mallikarjuna (Journal of Naval Architecture and Marine Engineering, 2016)
This article numerically studies for multi-physical transport of an optically-dense, free convective incompressible non-Newtonian second grade fluid past an isothermal, impermeable horizontal circular cylinder. The governing boundary layer equations for momentum and energy transport, which are parabolic in nature, have been reduced to non-similarity non-linear conservation equations using appropriate transformations and then solved numerically by employing with most validated, efficient implicit finite difference method with Keller box scheme. The numerical code is validated with previously existing results and found to be very good agreement. The results are reported graphically and in tabular form for various physical parameters; Deborah number, Prandtl number and thermal radiation on flow velocity and temperature profiles. Furthermore, the effects of these parameters on non dimensional wall shear stress (skin friction) and surface heat transfer rate (Nusselt number) are also investigated. Increasing the Deborah number reduces velocity profile, skin friction and Nusselt number where as it enhances the temperature profile. Increasing Prandtl number decelerates the flow velocity, temperature and skin friction but Nusselt number enhances considerably. Increase in radiation parameter retards the flow velocity, temperature profiles and skin friction. But Nusselt number enhances markedly with increase in radiation parameter. Applications of the model arise in polymer processing in chemical engineering, metallurgical material processing.